Ethical issues in training program : perception, ethical judgement and values held by trainers in Telekom Training Center (TTC) - Yusof, Mujahid (1998)
This case study was done in order to have an in-depth knowledge of ethical issues in training program. The aims of the studies are related to understand the perception of ethics held by the trainers and how they come to make decision base on ethical calculation. The studies also aims at looking into a deep understanding of the role of values in relation with ethical practice and the way trainers deals with their clients. Methods to gain access to the information were done through interviews with the trainers involved. From the interviews data was analyzed according to their themes. Telekom Training College being an established training institution for Telekom Malaysia Berhad was chosen to be the sample of study. Trainers in TTC have long been engaged in technical, skill and motiyational training program serving the parent company. However, in the findings, ethical issues are still in vague to the perception of the trainers. It's trainers perceived ethical issues on the surface of it, not in the depthness and the intensity of the problem. It was also found that TTC's trainers were dedicated to their work in pursuance of quality and professionalism. Ethics in the findings has close association with being professional. The relationship of the two bears the same characteristic, the only different is that being professional is driven strongly by the organizational rule and procedures whereby being ethical is strongly driven by intuition, integrity and values that one held as esteem.